Convergent patterns of structural brain changes in rapid eye movement sleep behavior disorder and Parkinson's disease on behalf of the German rapid eye movement sleep behavior disorder study group. Issue 3 (25th September 2020) - Holtbernd, Florian; Romanzetti, Sandro; Oertel, Wolfgang Hermann; Knake, Susanne; Sittig, Elisabeth; Heidbreder, Anna; Maier, Andrea; Krahe, Janna; Wojtala, Jennifer; Dogan, Imis; Schulz, Jörg Bernhard; Schiefer, Johannes; et al.
Abstract: Study Objectives: Rapid eye movement sleep behavior disorder (RBD) is considered a prodromal state of Parkinson's disease (PD). We aimed to characterize patterns of structural brain changes in RBD and PD patients using multimodal MRI. Methods: A total of 30 patients with isolated RBD, 29 patients with PD, and 56 age-matched healthy controls (HC) underwent MRI at 3T, including tensor-based morphometry, diffusion tensor imaging, and assessment of cortical thickness. Results: RBD individuals showed increased volume of the right caudate nucleus compared with HC, and higher cerebellar volume compared with both PD subjects and HC. Similar to PD subjects, RBD patients displayed increased fractional anisotropy (FA) in the corticospinal tracts, several tracts mainly related to non-motor function, and reduced FA of the corpus callosum compared with HC. Further, RBD subjects showed higher FA in the cerebellar peduncles and brainstem compared with both, PD patients and HC. PD individuals exhibited lower than normal volume in the basal ganglia, midbrain, pedunculopontine nuclei, and cerebellum. In contrast, volume in PD subjects was increased in the thalamus compared with both HC and RBD subjects. Conclusions: We found convergent patterns of structural brain alterations in RBD and PD patients compared with HC. The changes observed suggest a co-occurrence of neurodegeneration and compensatory mechanisms that fail with emerging PD pathology. Our findings strengthen the hypothesis of RBD and PD constituting a continuous disease spectrum.